2011
DOI: 10.1308/003588411x12851639107791
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics – cutting the cord on umbilical infections

Abstract: INTRODUCTION Surgical site infections (SSIs) are a significant cause of postoperative morbidity with laparoscopic surgery associated with lower SSI rates. However, a departmental change in our unit to increased laparoscopic colorectal surgery resulted in increased wound infection rates at umbilical specimen extraction sites, the cause of which we attempted to elucidate. SUBJECTS AND METHODS Prospectively collected data over an 18-month period (April 2008 to September 2009) for laparoscopic colorectal operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A suggested criticism to transumbilical incisions is the increased rate of surgical-site infection due to the propensity of the umbilicus to microbacterial colonization. 33 Avoiding umbilical incision was considered beneficial in reducing surgicalsite infection. 9 However, Hamzaoglu et al 34 concluded that umbilical flora is not responsible for trocar site infections.…”
Section: Discussionmentioning
confidence: 99%
“…A suggested criticism to transumbilical incisions is the increased rate of surgical-site infection due to the propensity of the umbilicus to microbacterial colonization. 33 Avoiding umbilical incision was considered beneficial in reducing surgicalsite infection. 9 However, Hamzaoglu et al 34 concluded that umbilical flora is not responsible for trocar site infections.…”
Section: Discussionmentioning
confidence: 99%
“…According to several authors, the initiation of pneumoperitoneum is frequently considered the most challenging phase of laparoscopy. This step carries numerous potential complications, irrespective of whether the closed or open technique is employed, which may include vascular and visceral injuries ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, transumbilical incisions pose a risk of increased surgical site infections due to the umbilicus's susceptibility to bacterial colonization ( 4 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The literature on preoperative umbilical cleanliness focuses on reducing the microbial load of the umbilicus in view of preventing surgical site infections (SSIs), which occur more frequently at the umbilicus than other laparoscopic port sites. 3,4 Preoperative antibiotics and 'care bundles' containing items such as antiseptic body wash, bowel preparation and information leaflets have shown varying effectiveness in preventing SSIs in general, [5][6][7][8][9] and it has been suggested that such interventions may be more clinically and cost-effective if they were concentrated in intrinsically dirty areas of the body. 4,10,11 To date, interventions that target gross contaminants of the umbilicus have not been studied, despite having clear practical implications for surgeons and the potential to reduce SSIs by optimising the activity of intraoperative skin antisepsis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Preoperative antibiotics and 'care bundles' containing items such as antiseptic body wash, bowel preparation and information leaflets have shown varying effectiveness in preventing SSIs in general, [5][6][7][8][9] and it has been suggested that such interventions may be more clinically and cost-effective if they were concentrated in intrinsically dirty areas of the body. 4,10,11 To date, interventions that target gross contaminants of the umbilicus have not been studied, despite having clear practical implications for surgeons and the potential to reduce SSIs by optimising the activity of intraoperative skin antisepsis. Surgeons' strategies to prevent SSIs vary greatly, 12 and more research is required to standardise preoperative management.…”
Section: Introductionmentioning
confidence: 99%